A Systematic Review of Reviews of Correctional Mental Health Services Using the STAIR Framework - Simpson, Alexander I. F.; Gerritsen, Cory; Maheandiran, Margaret; Adamo, Vito; Vogel, Tobias; Fulham, Lindsay; Kitt, Tamsen; Forrester, Andrew; Jones, Roland M. (Frontiers in Psychiatry, 2022)
Background: Rising demand for correctional mental health services (CMHS) in recent decades has been a global phenomenon. Despite increasing research, there are major gaps in understanding the best models for CMHS and how to measure their effectiveness, particularly studies that consider the overall care pathways and effectiveness of service responses. The STAIR (Screening, Triage, Assessment, Intervention and Re-integration) model is an evidence-based framework that defines and measures CMHS as a clinical pathway with a series of measurable, and linked functions. Method: we conducted a systematic review of the reviews of CMHS elements employing PRISMA guidelines, organised according to STAIR pillars. We assessed the quality of included studies using the AMSTAR-2 criteria. Narrative reviews were read and results synthesised. Results: we included 26 review articles of which 12 were systematic and/or meta-analyses and 14 narrative reviews. We found good evidence to support screening and triage methods and some to support specific psychosocial interventions. Conclusions: The STAIR framework is a useful way to organise the extant literature. More research is needed on interventions, assessment systems, care pathway evaluations and reintegration models.